The complete mitochondrial genome of Pseudomugil furcatus (Atheriniformes: Pseudomugil) and phylogenetic studies of Atheriniformes - Qi Wang; Jian Chen; Zengliang Miao; Youkun Huang; Fang Meng; Kehua Zhu; Bingjian Liu; Yifan Liu (Mitochondrial DNA. Part B. Resources, 2020)
Complete mitochondrial genome of the atheriniform fish Pseudomugil furcatus was characterized in this study. The whole mitogenome was 16,753 bp in size and consisted of 13 protein-coding genes (PCGs), 22 tRNAs, 2 rRNAs genes, a control region, and origin of light-strand replication. The proportion of coding sequences with a total length of 11,499 bp was 68.64%, which encoded 3869 amino acids. The base composition of the genome was 27.00% for A, 27.31% for C, 15.56% for G, and 30.13% for T. All PCGs started with ATG, ATP8, ND3, ND5, and ND6 ended with TAG, whereas CO2, ATP6, ND4 ended with a single T, the other PCGs commonly ended with TAA. The length of 12S ribosomal RNA was 948 bp, while that of 16S ribosomal RNA was 1744 bp. The control region (D-loop) ranging from 15,774 to 16,753 bp was 980 bp in size. The complete mitochondrial genome sequence provided here could be a useful information for the management of P. furcatus.